Biodiversity and categories of insects on lucerne crop at El-Outaya Bio-Resources station (CRSTRA-Biskra, Algeria) - Bengouga, Khalila; Taharchaouche, S; Bettiche, F; Bozdoğan, H (ENTOMOLOGIA HELLENICA, 2026)
Lucerne (Medicago sativa L.) is the main forage crop cultivated in the El-Outaya plain (Biskra, Algeria); however, information on the associated insect community remains limited for the region. Studying insects associated with this crop allows an assessment of their roles and ecological importance within the production system. This study aims to assess insect diversity, functional guild composition, and ecological roles within a pesticide-free lucerne agro-ecosystem. Insects were sampled weekly during the 2018 growing season, using circular yellow water traps, placed in a lucerne field and an adjacent bare-ground control. A total of 4655 insect specimens were collected and found to represent 80 species, 80 genera, 47 families, and seven orders. The main functional groups recorded were phytophagous species (47.5%), entomophagous (27.5%), and pollinators (13.75%), while detritivorous, hematophagous, scavengers, and saprophagous species accounted altogether for 11.25%. Most phytophagous species belonged to the order Hemiptera, whereas beneficial insects were mainly Hymenoptera. The Shannon–Wiener diversity index was higher in lucerne (H′ = 1.415) than in the bare control (H′ = 1.137), indicating the positive effect of crop presence on insect diversity. Long-term lucerne cultivation (approximately 10 years), providing both favourable microclimate and abundant nutritious food, under pesticide-free conditions, likely promoted the establishment of a structurally diverse and functionally balanced insect community consisting mainly of pollinators and phytophagous species, which in turn support predator populations. These findings provide baseline data for integrated pest management strategies and highlight the ecological value of lucerne agro-ecosystems in arid regions. Key words: Medicago sativa, beneficial insects, entomofauna, phytophagous insects .